COMPARISON ACCURACY OF WORD EMBEDDING WORD2VEC, GLOVE, DAN FASTTEXT USING SUPPORT VECTOR MACHINE FOR SENTIMENT ANALYSIS SPOTIFY APP REVIEWS - Margaretha Anjani, (2023)
Spotify is an application that is used as a digital audio streaming service platform that presents a variety of music and podcasts and can be downloaded for free on the Google Play Store. Reviews are a feature of the Google Play Store that can be used by users to rate an application. The reviews that an app can receive may affect the users who will download the app. Characteristics of unstructured review texts will be a challenge in the text processing process. To produce a valid sentiment analysis, it is necessary to apply word embedding. The data set that is owned is divided by a ratio of 80:20 for training data and testing data. The method used for the expansion of the Word2Vec, GloVe, and FastText features and the method used in the classification is the Support Vector Machine (SVM). The three word embedding methods were chosen because they can capture the semantic, syntactic, and contextual meanings around words when compared to traditional engineering features such as Bag of Word. The best performance evaluation results show that the GloVe model produces the best performance compared to other word embeddings with an accuracy value of 85%, a precision value of 90%, a recall value of 79%, and an f1-score of 85%.